The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1371/journal.pone.0125245
|View full text |Cite
|
Sign up to set email alerts
|

Multilocus Sequence Typing of Pathogenic Candida albicans Isolates Collected from a Teaching Hospital in Shanghai, China: A Molecular Epidemiology Study

Abstract: Molecular typing of Candida albicans is important for studying the population structure and epidemiology of this opportunistic yeast, such as population dynamics, nosocomial infections, multiple infections and microevolution. The genetic diversity of C. albicans has been rarely studied in China. In the present study, multilocus sequence typing (MLST) was used to characterize the genetic diversity and population structure of 62 C. albicans isolates collected from 40 patients from Huashan Hospital in Shanghai, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 17 publications
4
15
0
Order By: Relevance
“…Similarly, these clades contain the fewest strains in the global C. albicans MLST database. No isolates in Clade 13 were found in studies from Chinese regions such as Beijing 37 , Chengdu 38 , Shanghai 39 , 40 , Shenyang 41 , and Taiwan 42 44 . Several earlier studies found strong evidence for a geographic influence in the low representation of some clades in certain regions of the world.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, these clades contain the fewest strains in the global C. albicans MLST database. No isolates in Clade 13 were found in studies from Chinese regions such as Beijing 37 , Chengdu 38 , Shanghai 39 , 40 , Shenyang 41 , and Taiwan 42 44 . Several earlier studies found strong evidence for a geographic influence in the low representation of some clades in certain regions of the world.…”
Section: Discussionmentioning
confidence: 99%
“…In the global database, most Clade 19 isolates were from Asian subjects (China, South Korea, Iran, Kuwait). This clade was first described as clade New 1 by Wu 40 in Shanghai, China.…”
Section: Discussionmentioning
confidence: 99%
“…The main source of invasive C. albicans was confirmed to originate from the endogenous mycobiota (6,130,140,141). Indeed, identity between isolates from blood and colonized anatomical sites was almost always observed, leading to the conclusion that nosocomial transmission between patients is likely a rare event (141,142), even if an outbreak is suspected (143), although some authors have reported nosocomial transmission in hospital environments (144)(145)(146)(147)(148). MLP typing has also been used to track the origin of graft site candidiasis after kidney transplantation (149).…”
Section: Candida Yeasts Candida Albicansmentioning
confidence: 99%
“…12 Some STs were the same among isolates from different patients, supporting nosocomial transmission among patients. 10,16 The differences in the number of STs identified in this study compared to other studies may have been the result of different geographic regions. 26,27 Moreover, the differences in the STs identified among the isolates from Shenzhen People's Hospital and other Chinese hospitals 10,15 suggest that the genetic complexity is different among the communities of C. albicans in different hospitals.…”
Section: Albicans Strainsmentioning
confidence: 56%
“…9 Molecular biology typing methods, such as MLST and MLVA, are very useful for epidemiological investigation and nosocomial infection surveillance of C. albicans in hospital wards. 10 Indeed, MLST is performed easily and can be used to group C. albicans isolates in a similar way to Ca3 Southern hybridization. 11 It has been used to study the geographic distribution, 12e14 population structure, 13 infection regions, 15 prevalence, 15 diversity, 16 microevolution, 10,16 genetic basis of pathogenicity, 17 and drug resistance 13,18 of C. albicans.…”
Section: Introductionmentioning
confidence: 99%